On the Onset of Hydrothermal Convection in Porous Media in the Presence of Creeping Faults: Numerical Stability Analysis and Geological Applications - Tung, Rebecca Li Jia (Curtin University, 2018)
This thesis presents the effects of shear heating generated by creeping faults on the onset and pattern of hydrothermal convection. The implementation of a numerical stability analysis using the pseudo-arclength continuation method shows that imperfect bifurcation cases can stem from geometrical asymmetry and inhomogeneous material properties. This workflow was applied to a case study of a geothermal reservoir in Soultz-sous-Forêts and emphasises the necessity for a fully-coupled thermal-hydraulic-mechanical-chemical (THMC) approach in geothermal settings.